The Heart is Deceitful Above All Things Based on the Book by JT LeRoy - LeRoy, J. T. (Tartan Video, 2005)
This disturbing and moving film is based on the autobiographical stories of JT LeRoy, about a boy growing up in horrific conditions that combine the dangers of drugs, squalor, abuse and mind-control religion ... Artful and stylish, Argento's acting and filmmaking are edgy, authentic and rather nuts. The film is a feast (or maybe an assault) on the senses with light and colour, sound and texture, grimy rawness and goofy effects. Several scenes imply truly horrific assaults that are more memorable because Argento shows such restraint, letting us feel the pain more deeply because we have to imagine it. [www.shadowsonthewall.co.uk]
Keywords: DVD-Video